Semantics Analysis of Sentences, Utterances, and Presuppositions in Short Story: Two Kinds by Amy Tan - Aqilah Balqis Wardina; Hilma Safitri; Fildzah Zahirah; Jasmine Naya Shavia Chairunnisa; Riana Anggraini Bessi (INDO PUBLISHING, 2025)
This research examines sentence utterance and presupposition, as represented in Amy Tan's short story